Mineral Perspectivity Mapping in the Montana Region Based on a Combination of Variations in Gravity, Magnetic, and Geochemical Data Using Likelihood Ratio and Fuzzy Logic Methods - Adib, Jauhar Maknun (Himpunan Ahli Geofisika Indonesia (HAGI), 2024)
Montana is a province in the United States which is nicknamed the